Distinguishing the Chinese materia medica Tiepishihu from similar Dendrobium species of the same genus using histological and microscopic method. Issue 7 (17th March 2017) - Yu, Kun‐Zi; Yan, Hua; Tai, Hai‐Chuan; Zhang, Nan‐Ping; Cheng, Xian‐Long; Guo, Zeng‐Xi; Ma, Shuang‐Cheng; Wei, Feng
Abstract: The Chinese Materia Medica, Tiepishihu, used as a tonic for over one thousand years, is a well‐known precious medicine in China. According to the Chinese Pharmacopoeia, its source is the species Dendrobium officinale Kimura et Migo, which is distinguished from other species in Dendrobium genus. However, these species from the same genus are similar with Tiepishihu and caused confusion in the market. To find a quick and simple method to distinguish Tiepishihu from other similar species, histologic and microscopic methods were combined together to investigate the transverse section of stem of Tiepishihu and other similar species. Phloroglucinol test solution with hydrochloric acid was used to reveal the lignified tissue by staining the transverse section of Tiepishihu and similar species. Results revealed the unique identification characteristics to distinguish Tiepishihu from similar species, which were difficult to distinguish by other methods. The identification characteristics of Tiepishihu include the cells of vascular bundle sheath were stained red, parenchyma cells were not stained red. What's more, other species can be distinguished from each other with microscopic and histological characteristics. These characteristics proved stable and can be easily observed by normal light microscopic examination. This method is rapid, accurate, stable, and inexpensive. Abstract : Establish a quick and simple method to distinguish Tiepishihu from other 11 species by combining histologic and microscopic methods together. Eleven species in the same genus can be distinguished from each other with microscopic and histological characteristics.